Spatial arrangement for sesame cultivars - Almeida, Tanismare Tatiana de; Oliveira, Andréa dos Santos; Cruz, Pablo Muniz da; Bárbara, Cláudio das Neves Vieira; Santos, Fernando André Silva (Revista de Ciências Agroveterinárias, 2025)
This research evaluated the impact of different population densities and spacing on the agronomic characteristics of the Trebol and K3 sesame cultivars. The experiment was conducted at EMPAER's experimental unit in Cáceres, between March and July 2022, using randomized block design with twelve treatments and three replications. The treatments varied in spacing between 0.20 and 0.80 meters between the rows, and the characteristics analyzed included plant height, insertion of the first pod, number of pods per plant, number of seeds per pod, estimated yield, lodging index, purity analysis, determination of the weight of a thousand seeds, germination test and first germination count and germination speed index. The results indicated that the 0.80 m spacing favored plant development, especially related to height and number of pods, with the K3 cultivar standing out as the most productive. The phenotypic correlation analysis showed that the lodging index was the most relevant variable in determining the productivity of the Trebol cultivar, while plant height was the main variable for the K3 cultivar. It concluded that the 0,80 m row spacing is beneficial for sesame productivity, especially for the K3 cultivar, and that plant density directly influences the architecture and productive efficiency of the cultivars evaluated.